FORMULASI SEDIAAN SABUN CAIR EKSTRAK DAUN SIRIH HIJAU (Piper battle folium L.) DAN EKSTRAK BAWANG PUTIH (Allium sativum L.) SEBAGAI ANTIJAMUR Candida albicans - Nurul Marfu'ah, Rohmah Madya Ayu Fitriana, Solikah Ana Estikomah, (Pharmaceutical Journal of Islamic Pharmacy, 2018)
Islam is a religion that likes cleanliness, in case of body hygiene, clothing, and environment. One of the diseases that arise because it does not keep the body clean is white discharge. Piper bettle folium and Alium sativum are some of the natural ingredients that has the potential as an antifungal. This research aims to see the effect of antifungal Candida albicans extract of Piper bettle folium and Alium sativum after formulated as a liquid soap preparation. Liquid soaps are made by hot process methods with 3 formulations of combination of Piper bettle folium and Alium sativum extract with a ratio of 1) 25%: 75% 2) 50%: 50% 3) 75%: 25%. The evaluation of liquid soap include organoleptic examination, pH, high foam, moisture content, homogeneity, and antifungal power test against Candida albicans fungus. The results of the testing of liquid soap quality of green betel leaf extract and garlic have met the standards SNI (Indonesia’s National Standards) set for the manufacture of liquid soap.The results showed that liquid soap extract of green betel leaf and garlic have antifungal activity against Candida albicans. The result of formulation with the highest inhibition zone is formulation 3 and formulation with the lowest inhibition zone is the formulation 1. The test of this liquid soap activity is higher than fluconazole as the positive control and liquid soap of female area spread in the market.